Biocarriers facilitated gravity-driven membrane filtration of domestic wastewater in cold climate: combined effect of temperature and periodic cleaning - Hube, Selina (2023)
In this study, two lava stone biocarrier facilitated gravity-driven membrane (GDM) reactors were operated at ~8 °C and ~22 °C in parallel for treating primary wastewater effluent. Although the biocarrier reactor at 8 °C displayed less efficient removals of biodegradable organics than that at 22 °C, both GDM systems (without cleaning) showed comparable fouling resistance distribution patterns, accompanying with similar cake filtration constants and pore constriction constants by modelling simulation. Compared to the GDM at 8 °C, more foulants were accumulated on the GDM at 22 °C, but they presented similar soluble organics/inorganics contents and specific cake resistances. This indicated the cake layers at 22 °C may contain greater-sized foulants due to proliferation of both prokaryotes and eukaryotes, leading to a relatively less-porous nature. In the presence of periodic cleaning (at 50 °C), the cleaning effectiveness followed a sequence as ultrasonication-enhanced physical cleaning > two-phase flow cleaning > chemical-enhanced physical cleaning > physical cleaning, regardless of GDM operation temperature. However, significantly higher cake resistances were observed in the GDM system at 22 °C than those at 8 °C, because shear force tended to remove loosely-attached foulant layers and may compress the residual dense cake layer. The presence of periodic cleaning led to dissimilar dominant prokaryotic and eukaryotic communities in the cake layers as those without cleaning and in the lava stone biocarriers. Nevertheless, operation temperature did not influence GDM permeate quality, which met EU discharge standards.